Transcriptional Responses of Beauveria bassiana Blastospores Cultured Under Varying Glucose Concentrations - Mascarin, Gabriel Moura; Iwanicki, Natasha Sant’Anna; Ramirez, Jose Luis; Delalibera, Ítalo; Dunlap, Christopher A. (Frontiers in Cellular and Infection Microbiology, 2021)
Culturing the entomopathogenic fungus, Beauveria bassiana, under high glucose concentrations coupled with high aeration, results in a fungal developmental shift from hyphal growth to mostly blastospores (yeast-like cells). The underlying molecular mechanisms involved in this shift remain elusive. A systematic transcriptome analysis of the differential gene expression was preformed to uncover the fungal transcriptomic response to osmotic and oxidative stresses associated with the resulting high blastospore yield. Differential gene expression was compared under moderate (10% w/v) and high (20% w/v) glucose concentrations daily for three days. The RNAseq-based transcriptomic results depicted a higher proportion of downregulated genes when the fungus was grown under 20% glucose than at 10%. Additional experiments explored a broader glucose range (4, 8, 12, 16, 20% w/v) with phenotype assessment and qRT-PCR transcript abundance measurements of selected genes. Antioxidant, calcium transport, conidiation, and osmosensor-related genes were highly upregulated in higher glucose titers (16-20%) compared to growth in lower glucose (4-6%) concentrations. The class 1 hydrophobin gene (Hyd1) was highly expressed throughout the culturing. Hyd1 is known to be involved in spore coat rodlet layer assembly, and indicates that blastospores or another cell type containing hydrophobin 1 is expressed in the haemocoel during the infection process. Furthermore, we found implications of the HOG signaling pathway with upregulation of homologous genes Ssk2 and Hog1 for all fermentation time points under hyperosmotic medium (20% glucose). These findings expand our knowledge of the molecular mechanisms behind blastospore development and may help facilitate large-scale industrial production of B. bassiana blastospores for pest control applications.